Differences of Cyberloafing Behavior Outcomes on Men and Women Employees - Rauly Sijabat (Universitas Diponegoro, 2021)
The activities of reading news, chatting, viewing YouTube and Facebook or even status updates, Instagram, buying and selling online, to playing online games that are not related to work by using internet facilities are cyberloafing behaviors that are often carried out by employees. The limitations of previous research examining the impact of cyberloafing on work behavior empirically are still very limited. In addition, previous research that explains the occurrence of cyberloafing behavior also shows results that have not been established. Encouraged by these findings, this study aimed to examine the factors that explain cyberloafing behavior and its impact on employees' organizational behavior. To meet these objectives, an empirical model was developed with job characteristics and self-control variables as exogenous variables, job stress and cyberloafing as mediating variables and laziness as endogenous variables. Testing the influence between these variables was carried out with an analytical approach to Structural Equation Modeling (SEM) which used empirical data obtained through questionnaires as an interview guide to employee respondents in various fields of work. The results of data analysis showed that job characteristics, self control, and job stress were statistically proven to have an effect on cyberloafing behavior. Cyberloafing testing on negative organizational behavior, namely laziness also shows a real influence. In addition, the results of this study also show that there are differences in prevalence caused by cyberloafing behavior between male and female employees.